The theory of planned behavior and food choice questionnaire toward organic food of millennials in Vietnam - Hung Cuong Hoang; Miloslava Chovancová; Thi Que Huong Hoang (Global Business & Finance Review (GBFR), 2022)
Purpose: People have become more aware of environmental issues in their community, which has changed their food choices and how they buy green products, especially organic food. This study aimed to combine the food choice questionnaire (FCQ) and the theory of planned behavior (TPB) to examine the effect of the food choice questionnaire on customers' attitude related to the purchase intention of millennials in Vietnam. Design/methodology/approach: Data is collected from the three most prominent cities in Vietnam with 520 millennial respondents. The data is tested against the research model using structural equation modeling with SMART-PLS 3.2. Findings: The results indicate that the food choice questionnaire significantly affects customers' attitude toward the organic food of millennials in Vietnam. Moreover, the investigation confirmed the theory of planned behavior toward organic food purchasing of millennials in Vietnam. Research limitations/implications: For the limitation, organic food is studied in this investigation exclusively within a certain geographic area. For the academic implication, the contributions of this investigation are that it updates impacts of the food choice questionnaire based on the TPB in the context of millennials' intentions to purchase organic food in Vietnam. This study can enrich the literature on the combination of FCQ and TPB in the study of consumers' choice of organic food products. For the practical implication, businesses will comprehend the significance of the food choice questionnaire for millennials in Vietnam who intend to purchase organic food. For future research, the practitioners can use this study's model to examined in a variety of contexts, such as concerning eco-friendly items. In addition, this model can generally be applied to other food products such as conventional food, safety food, and products in restaurants or food stores. For academicians, the model can extend and develop additional constructs related to personality. For example, combining the big five personality traits, FCQ, and the TPB will further investigate which customer personality influences the intention to purchase food products. Originality/value: Contribute to the extension of TPB with the combination of FCQ and TPB and the study of millennials in Vietnam toward organic food purchasing intention.
Keywords: 650; Food choice questionnaire; Theory of planned behavior; Organic food; Millennials; Vietnam